РОЛЬ ДАННЫХ, ПРОДУКТОВ НАЦИОНАЛЬНЫХ СТАТИСТИЧЕСКИХ УПРАВЛЕНИЙ, В ПРИНЯТИИ СТРАНАМИ ПОЛИТИКИ НА ОСНОВЕ ДАННЫХ (пример из Ирана) (NeoEcon review, 2026)
The data products of national statistical offices play crucial roles in developing data-driven policies for social and economic growth of countries. The data products such as the results of population census and economic statistics, provide policymakers with a clear picture of the existing conditions, a standard toolkit for measuring progress made towards accomplishing the national development plans, and a roadmap for future development plans. Considering the fact that data are produced at high volumes, varieties and velocities on different subjects, the national statistical offices must adapt themselves to keep up with the speed of data production, analyzing data in real-time, and disseminating high-quality data to the users. The Statistical Centre of Iran which has been approved as the provider of official statistics on the I.R. Iran provides its users and policy makers in Iran with data products such as results of population and housing census, agriculture census, the results of various surveys on industries, Iran statistical yearbook and main indicators of the economy of Iran. These data products are appropriate measurements of the progress made for promoting the quality of social and economic lives of Iranian citizens. In this paper, the characteristics of data products and data policy of the Statistical Centre of Iran are explained, and their roles are assessed based on their contribution to assessment and preparation of the data-driven development policies in Iran. The results of this paper show that the data products of the Statistical Centre of Iran which measure various economic and social activities conducted in Iran are true images of existing situation and can be used as a roadmap for future development plans and upcoming national reports on achieving sustainable development goals.
Keywords: Data Product, Data Policy, National Statistical Offices